Accuracy of digital image enhancement in detection of vertical and horizontal root fracture - Maryam Ghazizadeh; Mahnaz Sheikhi; Maedeh Aminian; Mohammad Moein Ghazizadeh (Wolters Kluwer Medknow Publications, 2020)
Background: Two-dimensional intraoral radiography is the most common tool for recognizing root fractures. Improving the quality of images by means of enhancement tools can increase the recognition power of them. The aim of this study is to evaluate the effect of digital image enhancement on vertical and horizontal root fractures (HRFs) diagnostic accuracy. Materials and Methods: In this in vitro study, 100 human extracted teeth, involving 50 mandibular premolars and 50 maxillary incisors, were investigated. In total, 25 premolar teeth were vertically fractured and other 25 sound teeth served as testing group. According to the verified methods, 25 incisor teeth were fractured and other 25 teeth of this group served as testing ones. Following, by using the charge-coupled device sensor, preapical digital images were recorded. The original images were altered using reverse-contrast and colorization enhancement tools. Two different observers independently investigated all of the images. Receiver operating characteristic analysis was used to calculate the area under the curve (AUC) and sensitivity and specificity of all images. Data analyzde using receiver operating characteristic (ROC) analysis. Two-ways variance analysis was used to assess differences in the values (P = 0.05 ). Results: AUC and sensitivity and specificity related to the original, reverse-contrast, and colorized images were calculated (0.84, 0.64, 0.99), (0.84, 0.64, 0.96), and (0.82, 0.64, 0.92) respectively, for vertically root fractured images. AUC and sensitivity and specificity related to the original, reverse-contrast, and colorized images were calculated (0.49, 0.44, 0.56), (0.50, 0.44, 0.60), and (0.48, 0.48, 0.48), respectively, for horizontally root-fractured images. Conclusion: The results of the present study revealed that reverse-contrast and colorized enhancement filters cannot be used as critical methods in detecting in vitro vertical and HRF.